Letter from Arnold Beckman to Fred T. Williams - Beckman, Arnold O. (1944)
A letter from Arnold O. Beckman to Fred T. Williams, a patent advisor at the National Defense Research Committee. In this letter, Beckman reports on the delay in filing a patent for his carbon monoxide detecting "apparatus." This instrument would eventually become an important part of Beckman's fight against air pollution.
Keywords: Scientific apparatus and instruments; Carbon monoxide detectors; Air--Pollution; Carbon monoxide; Beckman Instruments, Inc.; Air--Pollution--Measurement